A method for preparing a battery
By uniformly mixing electrode active materials, conductive agents and thermoplastic binders, and preparing ultra-thick molded powder blocks through hot pressing technology, the problems of complex manufacturing processes of existing lithium-ion battery electrodes and difficult to improve energy density are solved, and super-thick electrodes with high strength and high energy density are achieved.
Patent Information
- Application Number
- CN202110433447.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-04-16
AI Technical Summary
The existing lithium-ion battery electrode sheet manufacturing process is complex, the energy density is difficult to improve, and the thick electrode design has problems such as poor strength and high proportion of inactive components.
By uniformly mixing the particulate material of the electrode active material, conductive agent and thermoplastic binder, and fiber material to form dry powder, and preparing ultra-thick molded powder blocks through hot pressing technology, the fiber material is used to enhance the mechanical strength and the thermoplastic binder to enhance the connection strength, and finally forming a high-strength ultra-thick electrode.
The process is simplified, the battery energy density is increased, the cost is reduced, and the uniform lithium replenishment and pore formation of ultra-thick electrodes is achieved without additional steps.
Smart Images

Figure CN115224366B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a method for preparing a battery. Background Art
[0002] The general process of manufacturing lithium-ion battery pole pieces is to mix active materials, binders and conductive agents to prepare slurry, then apply it on both sides of the copper or aluminum current collector, dry and remove the solvent to form pole pieces, and compact the pole piece particle coating to make it dense, and then cut or divide it into strips. At present, there are disadvantages such as complex manufacturing process and inability to further improve energy density.
[0003] Thick electrode design can significantly increase the load of active materials on the current collector, greatly increase the capacity of single cells, reduce the ratio of inactive components, thereby increasing the battery energy density and reducing costs. However, the currently published thick electrode preparation research methods have disadvantages such as poor electrode strength, complex manufacturing process, and unsuitability for large-scale industrial production. For example, Chinese patent application CN112467104A discloses a wet method for preparing thick lithium cobalt oxide electrodes. The electrode sheets are prepared by filtration, which has low production efficiency and is not easy to peel off from the electrode sheets and filter paper.
[0004] In addition, the increase in electrode thickness will extend the electron and lithium ion transmission path, increase the battery polarization impedance, and thus affect the electrochemical performance of lithium-ion batteries. The prior art discloses adding a small amount of magnetic material to the electrode slurry, and then applying a magnetic field to control the electrode microstructure during the electrode coating process. The above scheme can significantly reduce the pore tortuosity in the electrode thickness direction. However, the introduction of inactive substances will sacrifice energy density and pose safety risks. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing a battery, wherein the electrode active material, the granular material of the conductive agent and the thermoplastic binder, and the fiber material are uniformly mixed to obtain a dry powder, and the dry powder is hot-pressed to form an ultra-thick molded powder block, the mechanical strength of the molded powder block is enhanced by the fiber material, and the connection strength of the molded powder block is enhanced by the molten thermoplastic adhesive. The molded powder block is bonded and fixed to the collector shell to form an electrode assembly, and the electrode assembly is injected with liquid and assembled to obtain a battery. Through the preparation method of the present invention, button batteries or pouch batteries with ultra-thick electrodes of greater strength can be prepared in a simple manner, and uniform lithium replenishment and uniform pore formation of the ultra-thick electrodes can be achieved without adding additional steps.
[0006] The technical solution provided by the present invention is as follows:
[0007] According to the present invention, a method for preparing a battery is provided, the method comprising the following steps: (a) uniformly mixing raw materials to obtain dry powder, the raw materials comprising electrode active materials, conductive agents, and thermoplastic binder granular materials and fiber materials, wherein the mass ratio of the electrode active materials, conductive agents, thermoplastic binders and fiber materials is 1: 0.01-0.15: 0.02-0.15: 0.002-0.03; (b) hot pressing the dry powder, pressing and bonding the dry powder into a molded powder block by melting the thermoplastic binder, and the thickness of the molded powder block is The thickness of the battery is 0.2-3 mm, and the hot pressing temperature is 80-350°C; (c) coating a conductive glue on the current collecting shell cover of the battery, fixing the molded powder block on the current collecting shell cover to obtain an electrode assembly, and preparing the positive electrode assembly and the negative electrode assembly of the battery respectively; (d) placing the positive electrode assembly and the negative electrode assembly into a drying oven for drying; (e) injecting electrolyte into the positive electrode assembly of the battery and the negative electrode assembly of the battery respectively to infiltrate the molded powder block, placing a wet isolation layer between the positive electrode assembly and the negative electrode assembly, and packaging the positive electrode assembly and the negative electrode assembly into a battery.
[0008] In the above step (a), the raw materials at least include electrode active materials, conductive agents and thermoplastic binder granular materials and fiber materials, the electrode active materials, conductive agents and thermoplastic binders are granular materials or powdery materials, the particle size of the materials can be 0.05-200 μm, and the particle size of the materials can affect the mixing uniformity of the raw materials. The electrode active materials include positive electrode active materials and negative electrode active materials, the positive electrode active materials can be, for example, lithium iron phosphate, lithium manganese phosphate, lithium silicate, lithium iron silicate, sulfate compounds, sulfur-carbon complexes, sulfur, titanium sulfur compounds, molybdenum sulfur compounds, iron sulfur compounds, doped lithium manganese oxide, lithium cobalt oxide, lithium titanium oxide, lithium vanadium oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel aluminum oxide, lithium nickel cobalt manganese oxide or lithium iron nickel manganese oxide, etc., and the negative electrode active materials can be, for example, aluminum-based alloys, silicon-based alloys, tin-based alloys, germanium-based alloys, lithium titanium oxides, lithium silicon oxides, metal lithium powders or graphite that can be embedded with lithium. The conductive agent may be, for example, at least one of carbon black, graphene, carbon nanotubes, carbon fibers, amorphous carbon, and metal conductive particles. The thermoplastic adhesive may be, for example, at least one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, polycarbonate, polyamide, acrylic plastics, polysulfone, polyphenylene ether, and carboxymethyl cellulose. The fiber material may be at least one of polyester fiber, polyamide fiber, polyvinyl alcohol fiber, polyacrylonitrile fiber, polypropylene fiber, polyvinyl chloride fiber, glass fiber, metal fiber, and carbon fiber. The length of the fiber material may be 50 to 4000 μm, preferably 200 to 1000 μm, and the diameter may be 0.01 to 30 μm, preferably 0.05 to 0.3 μm. Raw materials in fine granular or powdered form may be mixed more evenly, and the mixing method may be, for example, ball milling, dry mixing, vibration mixing, and the like. The positive electrode active material, the conductive agent, the thermoplastic adhesive and the fiber material are uniformly mixed to obtain the positive electrode dry powder, and the negative electrode active material, the conductive agent, the thermoplastic adhesive and the fiber material are uniformly mixed to obtain the negative electrode dry powder. The thermoplastic adhesive can ensure the connection strength of the molded powder block generated later, and will not crack or crush during the preparation and assembly process. The fiber material can enhance the compressive strength and bending strength of the molded powder block generated later, reduce the brittleness of the molded powder block, increase its toughness, and improve the porosity of the molded powder block. The raw materials can also include functional materials such as metal lithium powder for uniform lithium supplementation and pore-forming material particles for pore formation. The particle size of the metal lithium powder can be 0.05-200μm, and the mass content can be 0.05%-0.2%. The particle size of the pore-forming material particles can be 0.05-200μm, and the mass content can be 1%-10%.
[0009] In the above step (b), the dry powder can be hot pressed using a hot press, the hot pressing pressure can be 4 to 25 MPa, and the hot pressing time can be 0.5 to 5 min (minutes). According to different shape requirements, different hot pressing molds can be used to press the shaped powder block into a circular, oval, square, rectangular, rhombus or trapezoidal shape. In the process of hot pressing the dry powder, the hot pressing temperature is 80 to 350 ° C. At this temperature, the thermoplastic adhesive uniformly dispersed in the dry powder melts and firmly bonds the powder together to form an integral block-shaped shaped powder block. The positive electrode dry powder is hot pressed into a positive electrode powder block, and the negative electrode dry powder is hot pressed into a negative electrode powder block. By controlling the mass ratio of the thermoplastic adhesive, even if the thickness of the powder block is thick, the powder block will not break and fall off, so an ultra-thick powder block with good shape retention can be prepared. When metallic lithium powder is added to the raw material, the hot pressing temperature can be set to be higher than the melting temperature of the metallic lithium powder, and the hot pressing temperature can be 200-350°C, so that the metallic lithium powder can be melted while hot pressing. In order to uniformly supplement the electrode active material with lithium, the metallic lithium should be evenly distributed between the electrode active material particles as much as possible. When the metallic lithium powder is melted, the molten metallic lithium can more evenly penetrate between the electrode active material particles, thereby achieving more uniform lithium supplementation of the electrode active material. When the granular material of the pore-forming material is added to the raw material, the pore-forming material can be at least one of ammonium bicarbonate, urea, ammonium carbonate, ammonium acetate and stearic acid, etc. The hot pressing temperature can be set to be higher than the thermal decomposition temperature of the pore-forming material, and the hot pressing temperature can be 100-350°C, so that the pore-forming material can be pyrolyzed while hot pressing, so as to form evenly distributed holes in the molded powder block. That is to say, in the hot pressing process of step (b), not only can the dry powder be hot pressed and formed, but also the purpose of uniform lithium supplementation and uniform pore formation can be achieved in the same step.
[0010] In the above step (c), a conductive glue is applied to the current collector shell cover of the battery, and then the molded powder block is fixed to the current collector shell cover to obtain an electrode assembly. The positive electrode powder block is fixed to the positive electrode current collector shell cover to form a positive electrode assembly, and the negative electrode powder block is fixed to the negative electrode current collector shell cover to form a negative electrode assembly. Since the molded powder block has a certain bonding strength, the shape and integrity of the powder block can be ensured without the need for additional shape retaining components during the assembly and fixation process. In the present application, the shell cover can be directly used as a current collector without the need to set up a separate current collector, thereby greatly simplifying the preparation process of the battery, reducing costs, and reducing the weight of the battery. The material of the current collector shell cover can be copper, aluminum, stainless steel, etc. The current collector shell cover can be bowl-shaped, and the conductive glue is applied to the inside of the current collector shell cover, and then the powder block is bonded and fixed inside the current collector shell cover. The current collector shell cover can be different from the shell cover of a traditional button battery, and the thickness of the current collector shell cover here can be as thin as less than or equal to 50μm. The current collector shell cover can also be a sheet of copper foil, aluminum foil, stainless steel foil, etc., and the thickness of the foil can be as thin as less than or equal to 10μm. Conductive glue is coated on one side of the current collector shell cover, and then the powder block is bonded and fixed to the side of the current collector shell cover coated with conductive glue. In addition, it is pointed out here that when multiple positive electrode powder blocks and multiple negative electrode powder blocks are cross-stacked and connected in parallel using positive electrode tabs and negative electrode tabs, the positive electrode powder block can be fixed to the positive electrode collector using conductive glue, and the negative electrode powder block can be fixed to the negative electrode collector using conductive glue. The positive electrode powder block on the end face can be fixed to the positive electrode collector shell cover, and the negative electrode powder block on the other end face can be fixed to the negative electrode collector shell cover.
[0011] In the above step (d), the positive electrode assembly and the negative electrode assembly are placed in a drying oven for drying. The drying temperature in the drying oven can be 50 to 100° C., and the drying time can be 1 to 3 hours.
[0012] In the above step (e), the positive electrode powder block of the positive electrode assembly is soaked in the electrolyte, the negative electrode powder block of the negative electrode assembly is soaked in the electrolyte, and the isolation layer is soaked in the electrolyte. When the positive electrode current collector shell cover of the positive electrode assembly and the negative electrode current collector shell cover of the negative electrode assembly are bowl-shaped, an insulating seal can be provided on the inner side of the bowl wall of the positive electrode current collector shell cover or the outer side of the bowl wall of the negative electrode current collector shell cover, and the isolation layer is placed between the positive electrode assembly and the negative electrode assembly, and then the bowl wall of the negative electrode current collector shell cover is placed on the inner side of the bowl wall of the positive electrode current collector shell cover and the positive electrode current collector shell cover and the negative electrode current collector shell cover are sealed and connected to form a button battery. When the positive electrode current collecting shell cover of the positive electrode assembly and the negative electrode current collecting shell cover of the negative electrode assembly are in sheet form, an insulating seal can be provided on the positive electrode current collecting shell cover or the negative electrode current collecting shell cover, an isolation layer is placed between the positive electrode assembly and the negative electrode assembly, and then the edge of the positive electrode current collecting shell cover and the edge of the negative electrode current collecting shell cover are directly sealed and connected to form a pouch-type battery, or the positive electrode current collecting shell cover and the negative electrode current collecting shell cover are pressed into a bowl shape and sealed and connected to form a button-type battery.
[0013] The advantages of the present invention are:
[0014] 1) Both the positive electrode active material layer and the negative electrode active material layer are in the form of ultra-thick pole pieces, which improves the storage capacity of the battery. By using a thermoplastic binder, the stability of the shape and structure of the ultra-thick pole pieces formed can be ensured;
[0015] 2) The electrode active material layer is directly prepared by hot pressing, and the current collector shell cover is directly used for current collection without the current collector, which reduces the battery cost and simplifies the complex process of battery preparation;
[0016] 3) Adding fiber-like substances to the electrode active material layer ensures the strength of the electrode active material layer and improves the porosity, which is beneficial to the absorption of the electrolyte and improves the electrochemical performance of the battery;
[0017] 4) Functional powders, such as pore-forming agents, lithium replenishing materials, etc., can be added during the preparation of the electrode active material layer. A one-step hot pressing operation can achieve the effects of pore-forming and lithium replenishing in the electrode active material layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a flow chart of a method for preparing a battery according to the present invention;
[0019] Figure 2 A schematic diagram of a method for preparing a button cell and a pouch cell according to the present invention;
[0020] Figure 3 It is a schematic diagram of another method for preparing a button battery according to the present invention.
[0021] Reference numerals list
[0022] 1——Positive electrode raw material dry powder
[0023] 2——Negative electrode raw material dry powder
[0024] 3——Positive electrode powder block
[0025] 4——Negative electrode powder block
[0026] 5. Aluminum foil
[0027] 6——Copper foil
[0028] 7——Cathode assembly
[0029] 8——Negative electrode assembly
[0030] 9——Positive electrode active material layer
[0031] 10——Negative electrode active material layer
[0032] 11 - Isolation layer
[0033] 12——Button battery
[0034] 13——Pouch battery
[0035] 14——Positive electrode current collector cover
[0036] 15——Negative electrode current collector cover DETAILED DESCRIPTION
[0037] The present invention will be further described below by way of embodiments in conjunction with the accompanying drawings.
[0038] Figure 1 The flowchart of the preparation method of the battery according to the present invention. First, the raw materials consisting of the granular materials of the electrode active material, the conductive agent and the thermoplastic binder and the fiber material are mixed into a uniform dry powder, and lithium powder, pore-forming materials, etc. can also be added to the raw materials. Then, a certain amount of dry powder is weighed, and the dry powder is hot-pressed using the mold of the hot press so that the dry powder forms an ultra-thick molded powder block with a certain bonding strength and mechanical strength, that is, the electrode active material layer. In this step, the molding, uniform lithium supplementation and pore formation of the electrode active material layer can be achieved in one step. Next, a conductive glue is applied to the sheet-shaped or bowl-shaped collector shell cover, and the molded powder block is fixed on the collector shell cover to form an electrode assembly. Subsequently, the electrode assembly is placed in a drying oven for drying. Finally, the electrode active material layer and the isolation layer of the electrode assembly are fully infiltrated with the electrolyte, and the positive electrode assembly and the negative electrode assembly are encapsulated to form a button or bag battery.
[0039] Figure 2 It is a schematic diagram of the preparation method of button cells and pouch cells according to the present invention. Prepare positive electrode raw material dry powder 1 and negative electrode raw material dry powder 2 respectively, and prepare positive electrode shaped powder blocks 3 and negative electrode shaped powder blocks 4 by hot pressing. Coat conductive glue on the sheet aluminum foil 5, fix the positive electrode shaped powder block 3 on the aluminum foil 5, and form a positive electrode assembly 7. Coat conductive glue on the sheet copper foil 6, and fix the negative electrode shaped powder block 4 on the copper foil 6 to form a negative electrode assembly 8. After the positive electrode assembly 7 and the negative electrode assembly 8 are dried, the positive electrode active material layer 9, the negative electrode active material layer 10 and the isolation layer 11 are infiltrated with electrolyte, the positive electrode active material layer 9 of the positive electrode assembly 7 and the negative electrode active material layer 10 of the negative electrode assembly 8 are placed opposite to each other, and the isolation layer 11 is placed between the positive electrode active material layer 9 and the negative electrode active material layer 10. In the final packaging process, the edge of the sheet copper foil 6 can be bent to form the side wall of the positive current collecting end cover and the edge of the sheet aluminum foil 5 can be bent to form the side wall of the negative current collecting end cover, and the side wall of the positive current collecting end cover and the side wall of the negative current collecting end cover are insulated and sealed to obtain a packaged button battery 12; or, the edge of the sheet copper foil 6 can be directly insulated and sealed with the edge of the sheet aluminum foil 5 to obtain a packaged pouch battery 13.
[0040] Figure 3 Schematic diagram of another method for preparing a button cell according to the present invention. Prepare positive electrode raw material dry powder 1 and negative electrode raw material dry powder 2 respectively, and prepare positive electrode shaped powder block 3 and negative electrode shaped powder block 4 by hot pressing. Coat conductive glue on the bowl-shaped stainless steel positive electrode current collector shell cover 14, fix the positive electrode shaped powder block 3 on the positive electrode current collector shell cover 14, and form a positive electrode assembly 7. Coat conductive glue on the bowl-shaped stainless steel negative electrode current collector shell cover 15, and fix the negative electrode shaped powder block 4 on the negative electrode current collector shell cover 15 to form a negative electrode assembly 8. After the positive electrode assembly 7 and the negative electrode assembly 8 are dried, the positive electrode active material layer 9, the negative electrode active material layer 10 and the isolation layer 11 are infiltrated with an electrolyte, and the positive electrode active material layer 9 of the positive electrode assembly 7 and the negative electrode active material layer 10 of the negative electrode assembly 8 are placed opposite to each other, and the isolation layer 11 is placed between the positive electrode active material layer 9 and the negative electrode active material layer 10. The side wall of the positive electrode current collecting end cover and the side wall of the negative electrode current collecting end cover are insulated and sealed to obtain a packaged button cell 12 .
[0041] Hereinafter, embodiments of the present invention will be described in detail.
[0042] Example 1
[0043] (a) Adding nickel-cobalt-manganese ternary material, carbon black, polyvinylidene fluoride and polyester fiber with a length of 2 mm and a diameter of 5 μm in a mass ratio of 1:0.044:0.055:0.011 into a planetary ball mill and mixing them uniformly to obtain a composite positive electrode powder; adding graphite, carbon black, polyvinylidene fluoride and polyester fiber with a length of 2 mm and a diameter of 5 μm in a mass ratio of 1:0.044:0.055:0.011 into a planetary ball mill and mixing them uniformly to obtain a composite negative electrode powder; (b) Weighing the positive electrode composite (c) using carbon nanotube aqueous conductive adhesive to bond the positive and negative electrode powder blocks to the bowl-shaped positive and negative electrode current collecting shell covers, respectively, to obtain positive and negative electrode assemblies; (d) placing the positive and negative electrode assemblies in an oven and heat treating them at 60°C for 2h; (e) injecting liquid into the positive and negative electrode assemblies respectively, and after the electrolyte is absorbed, adding a diaphragm and encapsulating and assembling button batteries.
[0044] Example 2
[0045] (a) lithium iron phosphate with a particle size of about 100 μm, graphene, polyvinyl chloride and glass fiber with a length of 500 μm and a diameter of 10 μm were mixed uniformly in a mass ratio of 1:0.03:0.1:0.01 to obtain a composite positive electrode powder; graphite, graphene, polyvinyl chloride, metallic lithium and glass fiber with a length of 500 μm and a diameter of 10 μm were mixed uniformly in a mass ratio of 1:0.03:0.1:0.001:0.01 to obtain a composite negative electrode powder; (b) 6.4 g of the positive electrode composite powder was weighed respectively. 3.2 g of the positive and negative electrode composite powders were placed in a square mold with a side length of 5 cm, and hot-pressed at 230°C with a pressure of 18 MPa to obtain positive and negative electrode shaped powder blocks; (c) the positive and negative electrode shaped powder blocks were fixed on the sheet-like positive and negative electrode current collecting shell covers using carbon nanotube aqueous conductive adhesive to obtain positive and negative electrode assemblies; (d) the positive and negative electrode assemblies were placed in an oven and heat treated at 70°C for 1 h; (e) the positive and negative electrode assemblies were injected with liquid respectively, and after the electrolyte was absorbed, a diaphragm was added, and the edges of the positive and negative electrode assemblies were insulated and sealed to obtain a pouch battery.
[0046] Example 3
[0047] (a) adding a nickel-cobalt-manganese ternary material with a particle size of about 10 μm, Ketjen black, polytetrafluoroethylene, ammonium bicarbonate, and polyester fiber with a length of 1000 μm and a diameter of 2 μm into a planetary ball mill in a mass ratio of 1:0.01:0.12:0.04:0.01 and mixing them uniformly to obtain a composite positive electrode powder; adding lithium titanate, Ketjen black, polytetrafluoroethylene, ammonium bicarbonate, and polyester fiber with a length of 1000 μm and a diameter of 2 μm into a planetary ball mill in a mass ratio of 1:0.01:0.12:0.04:0.01 and mixing them uniformly to obtain a composite negative electrode powder; (b) Weigh 0.28 g of positive electrode composite powder and 0.21 g of negative electrode composite powder, put them into a circular mold with a diameter of 14 mm, and hot-press at 350°C with a pressure of 10 MPa to obtain positive and negative electrode shaped powder blocks; (c) use carbon black aqueous conductive adhesive to bond the positive and negative electrode shaped powder blocks to the disc-shaped positive and negative electrode current collecting shell covers, respectively, to obtain positive and negative electrode assemblies; (d) put the positive and negative electrode assemblies into an oven and heat treat them at 80°C for 1.5 h; (e) inject liquid into the positive and negative electrode assemblies respectively, and after the electrolyte is absorbed, add a separator, and the positive and negative electrode assemblies are pressed into bowl shapes respectively and insulated and sealed to obtain button batteries.
[0048] Example 4
[0049] (a) lithium manganese oxide with a particle size of about 10 μm, metal powder, polyvinylidene fluoride, ammonium acetate and carbon fiber with a length of 2500 μm and a diameter of 0.3 μm were mixed uniformly in a mass ratio of 1:0.04:0.08:0.03:0.02 to obtain a composite positive electrode powder; graphite, metal powder, polyvinylidene fluoride, lithium metal, ammonium acetate and carbon fiber with a length of 2500 μm and a diameter of 0.3 μm were mixed uniformly in a mass ratio of 1:0.04:0.08:0.002:0.03:0.02 to obtain a composite negative electrode powder; (b) respectively weigh (c) using carbon nanotube aqueous conductive adhesive to bond the positive and negative electrode powder blocks to the sheet-like positive and negative electrode current collecting shells, respectively, to obtain positive and negative electrode assemblies; (d) placing the positive and negative electrode assemblies in an oven and heat treating them at 80°C for 1.5h; (e) injecting liquid into the positive and negative electrode assemblies respectively, and adding a separator after the electrolyte is absorbed, and sealing and insulating the edges of the positive and negative electrode assemblies to obtain a pouch battery.
[0050] The specific embodiments of the present invention are not intended to limit the present invention. Any person skilled in the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a battery, characterized in that: The preparation method comprises the following steps: (a) uniformly mixing raw materials to obtain dry powder, wherein the raw materials include electrode active material, conductive agent and thermoplastic binder granular material and fiber material, wherein the mass ratio of the electrode active material, conductive agent, thermoplastic binder and fiber material is 1:0.01-0.15:0.02-0.15:0.002-0.03; (b) hot pressing the dry powder by using a hot press and a hot pressing mold, and pressing and bonding the dry powder into a desired shaped powder block by melting the thermoplastic binder, wherein the thickness of the shaped powder block is The thickness of the molded powder block is 0.2-3 mm and the hot pressing temperature is 80-350°C; (c) coating a conductive glue on the collector shell cover, fixing the molded powder block on the collector shell cover to obtain an electrode assembly, and preparing a positive electrode assembly and a negative electrode assembly of the battery respectively; (d) placing the positive electrode assembly and the negative electrode assembly into a drying oven for drying; (e) injecting electrolyte into the positive electrode assembly of the battery and the negative electrode assembly of the battery respectively to infiltrate the molded powder block, placing a wet isolation layer between the positive electrode assembly and the negative electrode assembly, and packaging the positive electrode assembly and the negative electrode assembly into a battery.
2. The preparation method according to claim 1, wherein In the step (a), the raw materials also include metallic lithium powder; in the step (b), the hot pressing temperature is 200-350° C., so as to melt the metallic lithium powder so that the molten metallic lithium is evenly dispersed in the molded powder block.
3. The preparation method according to claim 1, wherein In the step (a), the raw materials also include granular materials of pore-forming materials, and the pore-forming materials are at least one of ammonium bicarbonate, urea, ammonium carbonate, ammonium acetate and stearic acid; in the step (b), the hot pressing temperature is 100-350°C, so as to thermally decompose the pore-forming materials so as to form evenly distributed holes in the molded powder block.
4. The preparation method according to claim 1, wherein The particle diameter of the particle material of the electrode active material, the conductive agent and the thermoplastic binder is 0.05 to 200 μm.
5. The preparation method according to claim 1, wherein The fiber material is at least one of polyester fiber, polyamide fiber, polyvinyl alcohol fiber, polyacrylonitrile fiber, polypropylene fiber, polyvinyl chloride fiber, glass fiber, metal fiber and carbon fiber.
6. The preparation method according to claim 5, wherein: The fiber material has a length of 50 to 4000 μm and a diameter of 0.01 to 30 μm.
7. The preparation method according to claim 1, wherein The thermoplastic adhesive is at least one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polystyrene, polyoxymethylene, polycarbonate, polyamide, acrylic plastic, polysulfone, polyphenylene ether and carboxymethyl cellulose.
8. The preparation method according to claim 1, wherein In the step (b), the hot pressing pressure is 4 to 25 MPa, the hot pressing time is 0.5 to 5 minutes, and the shape of the molded powder block is round, oval, square, rectangular, diamond or trapezoidal.
9. The preparation method according to claim 1, wherein: In the step (c), the current collecting shell cover is in sheet form, and the material of the current collecting shell cover is copper foil, aluminum foil or stainless steel foil; in the step (e), the edges of the current collecting shell covers of the positive electrode assembly and the negative electrode assembly are directly insulated and sealed, or the current collecting shell covers of the positive electrode assembly and the negative electrode assembly are pressed into a bowl shape and insulated and packaged.
10. The preparation method according to claim 1, wherein: In the step (c), the current collecting shell cover is bowl-shaped, and the material of the current collecting shell cover is copper, aluminum or stainless steel; in the step (e), the current collecting shell covers of the positive electrode assembly and the negative electrode assembly are insulated and packaged.
11. The preparation method according to claim 1, wherein: In the step (d), the drying temperature in the drying box is 50-100° C., and the drying time is 1-3 hours.
Citation Information
Patent Citations
Preparation method of lithium cobalt oxide thick electrode
CN112467104A
Electrode plate and preparation method and application thereof
CN111613775A
Manufacture for lithium ion secondary battery
JP1999288739A